Paradigmatic model of rural women's social entrepreneurship development using Grounded theory - Sanaz Shahvand; Maryam Omidi Najaf Abadi; Seyed Jamal Farajallah Hosseini (جغرافیا و توسعه, 2022)
Social entrepreneurship knowledge is critical for transforming the development of rural society and can be a good ground for the development and empowerment of women in rural areas. This study aims to analyze the factors affecting the entrepreneurship of rural women and present a paradigmatic model of social entrepreneurship development of rural women in Varamin County. The research method used in this research was qualitative, and among the conventional qualitative methods, the Grounded theory method was used. Participants included 11 experts and women entrepreneurs who were members of the Rural Micro Credit Fund of Varamin County who were selected and studied using the purposive sampling method. The primary way of data collection was semi-structured interviews that continued until the theoretical saturation point was reached. MAXQDA 12 software was used for data analysis and information processing. Internal validity of the research was measured using professors' points of view and long observations, external validity was measured by describing the obtained data, and the reliability of the study was measured by the triangulation method. The results showed that the most important critical aspect in social entrepreneurship is the socio-cultural aspect and then psychological aspect, economic aspect, environmental aspect, technology aspect and legal-political aspect, respectively. The relationship between the influential factors and the development of women's social entrepreneurship was presented in a paradigmatic model. A paradigm model including the components of causal conditions, contextual conditions, intervening conditions, interactive strategies and consequences for the development of social entrepreneurship of rural women was presented